2010
DOI: 10.1501/vetfak_0000002307
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological studies of equine herpesviruses 1 (EHV-1) and 4 (EHV-4) infections in working horses from the eastern Turkey

Abstract: Summary:The objective of this research was to determine the presence of equine herpesvirus types 1 (EHV-1) and 4 (EHV-4) antibodies in local horses from five provinces in the East Anatolia region of Turkey. Blood samples were collected from 405 nonvaccinated horses living in Van, Bitlis, Muş, Erzurum, and Iğdır, and were analyzed via a commercial enzyme-linked immunosorbent assay (ELISA). EHV-1-and EHV-4-specific antibodies were detected in 94 (23.2%) and 316 (78.0%) of the 405 tested sera, respectively. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Other studies conducted in our country confirm the existence of both viruses, in consistence with our findings, and indicated that they are still circulating among Türkiyes' horse population (Başkaya et al, 1968;Yılmaz et al, 1995;Gür and Yapici, 2008;Ataseven et al, 2010;Turan et al, 2012, Yildirim et al, 2015. Further studies are needed to investigate the prevalence and distribution of EHV-4 in the examined population.…”
Section: Black Sea Journal Of Health Sciencesupporting
confidence: 91%
See 2 more Smart Citations
“…Other studies conducted in our country confirm the existence of both viruses, in consistence with our findings, and indicated that they are still circulating among Türkiyes' horse population (Başkaya et al, 1968;Yılmaz et al, 1995;Gür and Yapici, 2008;Ataseven et al, 2010;Turan et al, 2012, Yildirim et al, 2015. Further studies are needed to investigate the prevalence and distribution of EHV-4 in the examined population.…”
Section: Black Sea Journal Of Health Sciencesupporting
confidence: 91%
“…Past research in our country has also highlighted the occurrence of EHV infections (Başkaya et al, 1968;Yilmaz et al, 1995;Mengi et al, 1996). The EHV-1 and EHV4 infections were presented in the indigenous horse population in the Eastern, North Eastern, Central and Western Anatolia of Türkiye (Gür and Yapici, 2008;Ataseven et al, 2010, Turan et al, 2012Yildirim et al, 2015). In diagnosing EHV-1 and EHV-4 infections in horses, samples are typically taken from fetal organs when nasal discharge, buffy coat, or abortion is observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are few reports about the prevalence of EHV in donkey farms in China and around the world. In this study, the serological survey of EHV- (2007)(2008) in Colombia and Ataseven (2010) in Turkey [24,25].…”
Section: Discussionmentioning
confidence: 99%